2018
DOI: 10.1021/acsami.8b15080
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Transport Properties of CdxBiyGe1–xyTe Alloys

Abstract: Band convergence has been proven as an effective approach for enhancing thermoelectric performance, particularly in p-type IV–VI semiconductors, where the superior electronic performance originates from the contributions of both L and Σ band valleys when they converge to have a small energy offset. When alloying with cubic IV–VI semiconductors, CdTe has been found as an effective agent for achieving such a band convergence. This work focuses on the effect of CdTe-alloying on the thermoelectric transport proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 66 publications
1
74
0
Order By: Relevance
“…The surface structure of the PI aerogel was smooth and flat, which may lead to decrease of contact angle. 33 Nevertheless, the surface structure of the F-PI aerogel was destroyed, the inside porous structure of the F-PI aerogel was partially preserved [ Figure S15(d)]. These results also confirmed that even the F-PI aerogel was presented in a depth of ca.…”
Section: Synthesis and Characterizationsupporting
confidence: 59%
See 3 more Smart Citations
“…The surface structure of the PI aerogel was smooth and flat, which may lead to decrease of contact angle. 33 Nevertheless, the surface structure of the F-PI aerogel was destroyed, the inside porous structure of the F-PI aerogel was partially preserved [ Figure S15(d)]. These results also confirmed that even the F-PI aerogel was presented in a depth of ca.…”
Section: Synthesis and Characterizationsupporting
confidence: 59%
“…In addition, the F-PI aerogels exhibited self-cleaning performance similar to the lotus effect. 33 As shown in the Supporting Information of Figure S3, the dust on the aerogel surfaces could be easily washed away by water.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…[27,28] Also, those with further suitable band-edge positions are highly expected for sunlight-driven water-splitting as efficient photocatalyst [29][30][31] due to their high surface ratio. Binary alloys of group IV-V elements (AB, A═Si, Ge and B═P, As) adopting layered structures [32][33][34] provide us another family of 2D materials. Based on the well-known top-to-down synthesizing strategy, few-layered group IV-V compounds have been experimentally realized.…”
mentioning
confidence: 99%